PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Pertanian yang terdaftar Di Bursa Efek Indonesia Periode Tahun 2013 – 2015) - Gultom, Calvin Pembri; Zirman, Zirman; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to investigate the influence of good corporate governance toward the activity of tax avoidance at agriculture companies which are registered in Indosesia Stock Exchange (BEI) in 2013-2015. The populations of this research are companies which have been officially registered in Bursa Efek Indonesia in 2013-2015. The samples were chosen by administrating purposive sampling methods. Thus, there are 45 samples selected. This study utilized doubled linear analysis by employing SPSS 24.0. The result of this study showed that there was significant influence on good corporate governance proxy which was the percentage of managerial ownership, the independent board of commissioners, toward the tax avoidance activity which was proxied with the Effective Tax Rate (ETR). In addition, the result of this research also demonstrated that the tax avoidance activity was not significantly influenced by the audit quality as well as audit committee.Keywords : managerial ownership, independent commissioner, audit quality, audit committee, good corporate governance, Effective Tax Rate (ETR)